2006
DOI: 10.1097/01.hp.0000225467.10064.34
|View full text |Cite
|
Sign up to set email alerts
|

A New Proposal for Monitoring Patients in Nuclear Medicine

Abstract: The measurement of exposure rates is fundamentally important in the release of patients given radioactive materials and for keeping the exposures of others as low as reasonable achievable. Similar measurement methodologies have generally been used for point and extended sources, but this approach may lead to methodological errors in calculating radiation dose estimates. In this study, nuclear medicine patients who received high activities of Na131I for therapy were monitored using different measurement methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
7
1
1
Order By: Relevance
“…This wide variety of ratio seems to be partly due to variability of tumor location and measurement geometry. These results are contrary to the observation by Siegel et al [27] and Willegagnon et al [28], who dealt with gamma radiation and observed that measured TEDE is lower than theoretical TEDE. To our knowledge, this is the first report that compares the theoretical TEDE with measured TEDE in Y-90 microsphere RET.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This wide variety of ratio seems to be partly due to variability of tumor location and measurement geometry. These results are contrary to the observation by Siegel et al [27] and Willegagnon et al [28], who dealt with gamma radiation and observed that measured TEDE is lower than theoretical TEDE. To our knowledge, this is the first report that compares the theoretical TEDE with measured TEDE in Y-90 microsphere RET.…”
Section: Discussioncontrasting
confidence: 99%
“…So, the actual radiation dose may be different from the theoretically calculated TEDE based on administered activity. The 'measured' exposure dose equivalent calculated by actual measurement of ambient exposure rate can be different from estimated 'theoretical' exposure dose [28]. According to our observation, the 'measured' TEDEs are generally higher than those of 'theoretical' TEDEs as the ratio of 'measured' TEDE to 'theoretical' TEDE (Dm/Dt ratio) is from 1.28 to 65.99 (Table 3).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The stay period of radioiodine administered patients solely depends upon the exposure rate measurement [4] by which the dose to others may be minimized [12,13]. If the administered radioiodine to the patient is more than 30 mCi, isolated hospitalization is necessary until the reduction of residual activity to 30 mCi or decline of the exposure rate to 50µSv/ hr (micro Sievert) at one meter from patient [14,15].…”
Section: Methodsmentioning
confidence: 99%